The Influence of Dapagliflozin on Foot Microcirculation in Patients with Type 2 Diabetes with and without Peripheral Arterial Disease-A Pilot Study - Božena Bradarić; Tomislav Bulum; Neva Brkljačić; Željko Mihaljević; Miroslav Benić; Božo Bradarić Lisić (MDPI AG, 2024)
The results of large cardiovascular studies indicate that SGLT-2 inhibitors may increase the risk of leg amputations. This study aims to investigate whether dapagliflozin therapy affects peripheral vascular oxygenation, i.e., microcirculation in the foot, as measured by transcutaneous oxygen pressure (TcPO2) in patients with type 2 diabetes (T2DM) and peripheral arterial disease (PAD) compared to patients without PAD. The patients with PAD were randomized into two groups. In the first 35 patients with PAD, dapagliflozin was added to the therapy; in the other 26 patients with PAD, other antidiabetic drugs were added to the therapy. Dapagliflozin was added to the therapy in all patients without PAD. TcPO2 measurement, Ankle Brachial Index (ABI), anthropometric measurements, and laboratory tests were performed. After a follow-up period of 119.35 days, there was no statistically significant difference in the reduction of mean TcPO2 values between the group with T2DM with PAD treated with dapagliflozin and the group with T2DM with PAD treated with other antidiabetic drugs (3.88 mm Hg, SD = 15.13 vs. 1.48 mm Hg, SD = 11.55, p = 0.106). Patients with control TcPO2 findings suggestive of hypoxia (TcPO2 < 40 mm Hg) who were treated with dapagliflozin had a clinically significant decrease in mean TcPO2 of 10 mm Hg or more (15.8 mm Hg and 12.90 mm Hg). However, the aforementioned decrease in TcPO2 was not statistically significantly different from the decrease in TcPO2 in the group with PAD treated with other diabetic medications (p = 0.226, p = 0.094). Based on the available data, dapagliflozin appears to affect tissue oxygenation in T2DM with PAD. However, studies with a larger number of patients and a longer follow-up period are needed to determine the extent and significance of this effect.